1995
DOI: 10.1080/00224545.1995.9711417
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Job Satisfaction

Abstract: The competing hypotheses of socialization, structural, and social role theories were used to investigate the possible existence of gender differences in job satisfaction. The hypotheses were tested in a sample of over 13,000 U.S. employees from approximately 130 organizations and divisions across a variety of industries. The organizations were clients of a North American-based management consulting company. T tests and effect sizes were calculated to test for the possible existence of group differences in job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 3 publications
5
83
1
7
Order By: Relevance
“…On the contrary, female writers' preference for the inclusive we builds a rapport with the reader and puts them at one with the reader. This is typical of women language, which according to Mason (1994), would consist of features that transmit a sense of cooperation and selflessness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, female writers' preference for the inclusive we builds a rapport with the reader and puts them at one with the reader. This is typical of women language, which according to Mason (1994), would consist of features that transmit a sense of cooperation and selflessness.…”
Section: Discussionmentioning
confidence: 99%
“…The former has the tendency to transmit a sense of togetherness and cooperation by equating themselves in their arguments (Mason 1994), while the latter seems to project an aura of dominance and authority by separating themselves from the reader (Leaper 1991, Mulac, Bradac & Gibbons 2001 As summarised in Table 5, only four key hedges were most often employed by learners, and they include should, would, may and most. Asian learners in general are very cautious and indirect in expressing their opinions (Ahmad 1995); thus, modals such as should, would and may would be common occurrences in their writing.…”
Section: Dia005m Uitmmentioning
confidence: 99%
“…Gencay (2007) did not find any meaningful correlation between gender and job satisfaction from his research Erol 1837 with P.E teachers. Mason (1994), in a research on gender effects on job satisfaction, found there was no meaningful correlation between gender and job satisfaction. This research is in parallel with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a study by Carleton and Clain (2012) suggest that there is greater job satisfaction among women but it was limited to married workers. In addition, using the competing hypotheses of socialization, structural and social role theories which were tested on a sample of 13000 US employees, across various industries, Mason (1995) asserted that US women and men in management apparently did not differ from one another in their factors of satisfaction at work. Inconsistencies in findings concerning the relationship between gender and job satisfaction may therefore be due to a variety of factors.…”
Section: Job Satisfaction and Gender Differencesmentioning
confidence: 99%